PKM. SOSIALISASI DAN PENDAMPINGAN PENELITIAN TINDAKAN KELAS PADA GURU SMP NEGERI 3 ABIANSEMAL BADUNG (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
Classroom action research is a good solution that must be applied in the classroom to overcome various problems that occur in the classroom. The main objective of this activity is to help teachers develop classroom action research proposals that are appropriate to the learning and educational problems experienced by teachers both inside and outside the classroom. Assistance in writing classroom action research which was carried out at SMP Negeri 3 Abiansemal Badung on June 26, 2021. The steps for implementing the assistance were: workshop implementation, assistance in the preparation of CAR, assistance in implementing CAR, and evaluation and reflection stages. Targets and outcomes are in accordance with the objectives of mentoring which have an impact on: (1) Providing solutions to problems that occur in schools, (2) Increasing creativity and innovation in learning activities. The results of the PKM were at first the teachers did not know about the making of CAR. With this mentoring activity, the teacher became aware of and understood the CAR activities in the classroom. By applying classroom action research, you can overcome the problems that exist in the classroom with the support of theory and journals. After mentoring was held for 3 times there was significant progress in the teacher's ability to write CAR